Economics of village production of N'Dama cattle in the Gambia - Itty, P.; Swallow, B.M.; Rowlands, G.J.; Agyemang, K.; Dwinger, R.H. (1993)
From biological data collected between January 1986 and December 1989, and economic data collected during 1988, 10-year projections of herd structure, production, and economic and financial returns were calculated for 13 village cattle herds at two village sites in the Gambia. The analyses indicate that village herds in the Gambia generated attractive economic returns despite their relatively low productivity. Financial returns varied: the average rate of return was just equal to the assumed opportunity cost of capital at Gunjur (a peri-urban site), while the returns were much higher at Keneba (a more rural site). At Keneba, average lactation offtake was higher and herding costs per animal were lower. Although returns were lower at Gunjur than at Keneba, they were still fair considering the few other investment alternatives available in rural areas of the Gambia. The main economic constraints to increased cattle production were the high costs of herding and the system of herd management that separates ownership from management and herding. As long as animals are fed by someone other than their owners, and as long as hired herders are paid in terms of the milk they collect from lactating cows, incentives to improved disease control and animal nutrition will continue to be distored.